Advanced prostatic carcinomas with low serum levels of prostate-specific antigen - Cerović Snežana J. (Vojnosanitetski Pregled, 2002)
The serum levels of prostate-specific antigen (PSA) represent a significant diagnostic and monitoring parameter of prostatic carcinoma (PC). The aim of the study was to establish correlation of serum PSA level in addition to grade, histological type, and clinical stage of PC in patients with normal or intermediary PSA serum level. In 37 untreated PC patients with preoperative serum PSA levels ranging between 0.1 and 9.6 ng/ml, paraffin-embedded tissue and serum samples were immunohistological studied and immunoassay for PSA was done. The most representative was poorly differentiated PC with D stage In serum samples from PC patients 27 (73.7%) normal (≤ 4.0 ng/ml), and 10 (27.3%) intermediate (4.1-10 ng/ml) PSA levels were found Immunohistochemistry, in 36 PC (97.3%) had demonstrated the expression of PSA. Our study results had shown low serum PSA levels in some patients with advanced poorly differentiated PC.